2020
DOI: 10.1371/journal.pone.0230339
|View full text |Cite
|
Sign up to set email alerts
|

Frailty, markers of immune activation and oxidative stress in HIV infected elderly

Abstract: People living with HIV-1 experience an accelerated aging due to the persistent and chronic activation of the immune system. This phenomenon conduces to immune exhaustion and precipitate immunosenescence. In general, frailty is defined as a syndrome of physiological degeneration in the elderly. Circulating naïve and memory T cells were studied by flow cytometry in non-frail and frail HIV-1-infected groups. Thymopoiesis, cell activation, senescence and cell proliferation were analyzed by CD31, HLA-DR/CD38, CD28/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 66 publications
2
19
0
Order By: Relevance
“…Over a half of our patients from the PLHIV cohort had at least one comorbidity, which is high considering the low average age of our patients. This finding has been described previously 8,9 and may be related to the known premature aging and frailty 23 that HIV infection produces, leading to the development of comorbidities at younger ages.…”
Section: Discussionsupporting
confidence: 80%
“…Over a half of our patients from the PLHIV cohort had at least one comorbidity, which is high considering the low average age of our patients. This finding has been described previously 8,9 and may be related to the known premature aging and frailty 23 that HIV infection produces, leading to the development of comorbidities at younger ages.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, a 2005 study found a significantly increased number of CD8+ T lymphocytes and CD8+CD28− lymphocytes in frail women versus pre-frail and non-frail women (Semba et al, 2005). A Spain study in the frail group concluded that the frequency of CD8+CD28−CD57+ was significantly elevated in comparison with the non-frail group [35], [36]. Some conditions also cause reduced CD4/CD8 ratio.…”
Section: Cd4mentioning
confidence: 99%
“…The primary drivers of frailty are due to dysregulation of stress responses that result in alterations of the endocrine, immune, and inflammatory systems. 3,14 Among persons who have been identified as frail, levels of hormones, such as growth hormone, insulin-like growth factor, sex steroids, and dehydroepiandrosterone sulfate, are decreased. 3 Alterations in these hormones can lead to decreases in muscle mass, strength, and mobility.…”
Section: Pathophysiologymentioning
confidence: 99%